Peran Pengelolaan Sumber Daya Manusia Dalam Meningkatkan Keberhasilan Program Kewirausahaan Di Sekolah - Wahira, Wahira; Anwar, Andi Ratu Ayuashari (Yayasan Abdurrauf Cendekia Nusantara, 2025)
Education is a key pillar in shaping superior human resources (HR) who are adaptive to the challenges of globalization and the industrial revolution 4.0. In this context, schools are not only required to produce graduates with strong academic achievements but also individuals who are independent, creative, and innovative through the development of entrepreneurship programs. The success of such programs is highly influenced by the effectiveness of HR management, particularly teachers and educators who play a crucial role in designing, implementing, and evaluating the entrepreneurship learning process. This study aims to identify the strategic role of HR management in enhancing the success of entrepreneurship programs in schools, to analyze the management aspects that significantly influence program effectiveness, and to provide an overview of HR management practices that can be implemented in the context of entrepreneurship education. The method applied is a literature review by examining theories, previous research findings, and HR management practices in schools. The analysis focuses on four main aspects: recruitment and placement of educators, training and competency development, motivation and well-being of HR, as well as program evaluation and monitoring. The theoretical framework of this study refers to the concept of HR management in education and theories of school-based entrepreneurship development. The findings indicate that well-planned and sustainable HR management is a determining factor in the success of entrepreneurship programs in schools. Recruitment of qualified educators, practice-based training, improvement of motivation and well-being, and systematic program evaluation contribute to the creation of effective entrepreneurship learning. Entrepreneurship programs supported by optimal HR management are proven to produce graduates who are not only academically competitive but also possess an entrepreneurial spirit that is independent, innovative, and adaptive to the dynamics of change. Abstrak: Pendidikan sebagai pilar utama dalam membentuk sumber daya manusia (SDM) yang unggul dan adaptif terhadap tantangan globalisasi serta revolusi industri 4.0. Dalam konteks ini, sekolah tidak hanya dituntut menghasilkan lulusan yang berprestasi akademik, tetapi juga individu yang mandiri, kreatif, dan inovatif melalui pengembangan program kewirausahaan. Keberhasilan program tersebut sangat dipengaruhi oleh efektivitas pengelolaan SDM, khususnya guru dan tenaga pendidik, yang berperan penting dalam merancang, melaksanakan, serta mengevaluasi proses pembelajaran kewirausahaan.Penelitian ini bertujuan untuk mengidentifikasi peran strategis pengelolaan SDM dalam meningkatkan keberhasilan program kewirausahaan di sekolah, menganalisis aspek-aspek pengelolaan yang berpengaruh signifikan, serta memberikan gambaran praktik manajemen SDM yang dapat diimplementasikan dalam konteks pendidikan kewirausahaan. Metode yang digunakan adalah studi literatur dengan menelaah teori, hasil penelitian terdahulu, serta praktik manajemen SDM di sekolah. Analisis difokuskan pada empat aspek utama, yaitu rekrutmen dan penempatan tenaga pendidik, pelatihan dan pengembangan kompetensi, motivasi dan kesejahteraan SDM, serta evaluasi dan monitoring program. Kerangka teoritis penelitian ini mengacu pada konsep manajemen SDM dalam pendidikan dan teori pengembangan kewirausahaan berbasis sekolah. Hasil kajian menunjukkan bahwa pengelolaan SDM yang terencana dan berkelanjutan terbukti menjadi faktor penentu keberhasilan program kewirausahaan di sekolah. Rekrutmen tenaga pendidik yang relevan, pelatihan berbasis praktik, peningkatan motivasi dan kesejahteraan, serta evaluasi program yang sistematis berkontribusi dalam menciptakan pembelajaran kewirausahaan yang efektif. Program kewirausahaan yang didukung oleh manajemen SDM yang optimal mampu melahirkan lulusan yang tidak hanya kompetitif secara akademik, tetapi juga memiliki jiwa wirausaha yang mandiri, inovatif, dan adaptif terhadap perubahan zaman. Kata kunci: Pengelolaan SDM, Kompetensi Guru, Manajemen Sekolah